Teste de Chika : um critério geral de divisibilidade - Shimokawa, Edivaldo Yuzo (2020)
The divisibility criteria are often learned in a mechanized way, often focusing only on solving exercises. However, this subject presents a wide field of action for the student to develop his mathematical reasoning through arithmetic. Motivated by the news that reverberated on social networks about a nigerian boy named Chika Offili, in this work we will briefly address how he started using the divisibility criterion, we will tell a little about the discovery of Chika, we will demonstrate the classic divisibility criteria, those that one learns in basic education, showing that for each prime number there is a different test which makes it difficult for the student to learn. Based on Chika’s idea, we will present a divisibility criterion that can be an alternative in teaching divisibility.